High Power Laser and Photobiomodulation in Oral Surgery: Case Report - de Araújo, Júlia Gomes Lúcio (J Lasers Med Sci, 2019)
Introduction: The labial frenum is a fold of mucous membrane that attaches the lip and the cheek to the alveolar mucosa, the gingiva, and the underlying periosteum. In some cases, its presence can cause a midline diastema, periodontal diseases related to food impaction, or retention of biofilm, among others. In such cases, lip frenectomy is indicated as treatment, which can be performed with a scalpel (conventional method), an electric scalpel, or a surgical laser. Objective: To show a clinical case performed at Laser Extension Project in Dentistry, Federal University of Maranhão grounded in a literature review. Case Presentation: A laser frenectomy was performed on a female patient, aged 20, who had a diastema between the upper central incisors and an indication for frenum removal. The high-power diode laser is excellent for procedures in soft tissue because its wavelength is well absorbed by hemoglobin and other pigments; its use also allows a reduction in the amount of anesthetic and medicines used. The parameters used were 2 W, in a continuous mode, 808 nm infrared emission; with delivery of the beam through optical fiber 300 μM; energy of 120 J; 20 pps. Conclusion: the high power diode laser allowed a satisfactory result, the procedure was safe, the technique was a simple one and of reduced clinical time, as mentioned in the literature. It is worth noting that the technique is dependent on the skill of the professional performing it.